BIMBINGAN KELOMPOK MODEL PERMAINAN BELAJAR BERSIKAP UNTUK MENINGKATKAN KEMAMPUAN PENYESUAIAN DIRI DI SEKOLAH SISWA - Dinar Mahdalena Leksana (Universitas Islam Lamongan, 2018)
The goal of this research was to test the effectiveness of using group guidance service with learn to behave game to increase the ability of self adjustment at school. This research was conducted by pre-test post-test one group design. The subject of this research were eight students of 7th graders at MTs Darrul Ma’arif Payaman, with low score of the ability of self adjustment at school. Data analysis technique used in this research was Wilcoxon’s signed rank test. It was found that there was a significant difference between the ability of self adjustment at school score before and after treatment. Based on the Wilcoxon test it was found that T count = 0, N = 8 with 0,05 significant level so T table = 4. It means T count < T table (0<4). So hypothesis of this research was accepted. It can be concluded that group guidance service with learn to behave game was an effective approach to help students to increase the ability of self adjustment at school.